Los mecanismos de control interno en las empresas del rubro ferretero de la ciudad de Iquitos, 2020 - Arias Manihuari, Helia Mercedes (2022)
The present research work had as general objective: To know the internal control mechanisms in the companies of the hardware sector of the city of Iquitos, 2020. The research is of a descriptive type and non-experimental design, likewise, the population was made up of 27 entrepreneurs of the hardware sector of the city of Iquitos, to whom a structured questionnaire with 17 items each under the Likert-type scale was applied. From the results obtained, it was concluded that the internal control mechanisms in the companies of the hardware sector is regular 44% since internal control manuals still need to be implemented, in addition they fail to provide adequate support to the functional processes that contribute to the activities, therefore, many entrepreneurs do not establish policies to control the operations of their company, in effect, entrepreneurs have difficulties to identify and analyze the risks, which hinders the development of control activities that in a certain way occur to supervise the person's work. Likewise, it was possible to identify that the control environment is 37% efficient, in addition, the risk assessment in the companies of the hardware sector is 48% regular, on the other hand, the control activities in the companies of the hardware sector is regular 52%. , on the other hand, the information and communication in the companies of the hardware sector is 41% regular, in terms of monitoring in the companies of the hardware sector it is 44% regular.